Maize VIVIPAROUS1 Interacts with ABA INSENSITIVE5 to Regulate GALACTINOL SYNTHASE2 Expression Controlling Seed Raffinose Accumulation - Zhang, Y.; Sun, Q.; Zhang, C.; Hao, G.; Wang, C.; Dirk, L. M.; Zhao, T.
Raffinose, an oligosaccharide found in many seeds, plays an important role in seed vigor; however, the regulatory mechanism governing raffinose biosynthesis remains unclear. We report here that maize W22 wild type (WT)seeds, but not W22 viviparous1 (zmvp1)mutant seeds, start accumulating galactinol and raffinose 28 days after pollination (DAP). Transcriptome analysis of the zmvp1 embryo showed that the expression of GALACTINOL SYNTHASE2 (GOLS2)was down-regulated relative to WT. Further experiments showed that the expression of ZmGOLS2 was up-regulated by ZmABI5 but not by ZmVP1, and it was further increased by the coexpression of ZmABI5 and ZmVP1 in maize protoplasts. ZmABI5 interacted with ZmVP1, while ZmABI5, but not ZmVP1, directly binds to the ZmGOLS2 promoter. Together, all of the findings suggest that ZmVP1 interacts with ZmABI5 and regulates ZmGOLS2 expression and raffinose accumulation in maize seeds.
Keywords: MAIZE; SEEDS; VIVIPAROUS; ABI5; GALACTINOL SYNTHASE; RAFFINOSE BIOSYNTHESIS